Exploring the causal effect of complement and IgA nephropathy—a Mendelian randomization study - Han Xu; Mengxiao Zou; Yichun Cheng; Shuwang Ge (Renal Failure)
IgA nephropathy, one of the most common primary glomerulonephritis worldwide, is still under investigation for its precise etiology. The widely accepted theory is the ‘four-hit model’ and subsequent complement and inflammatory responses. Recent studies have reported correlations between specific complement components and IgA nephropathy. However, the causal effects of genetically predicted complement components on IgA nephropathy require further elucidation. Our study aimed to determine the causal relationship between genetic predictors of complement and IgA nephropathy using the Mendelian randomization method. The primary analysis was initially conducted, examining heterogeneity and horizontal pleiotropy tests in each subgroup. Complement components with positive results were further analyzed using the MR-PRESSO test and co-localization analysis. Subsequently, the positive results were further analyzed using the cML-MA method to validate the previous studies. Finally, a Bi‑directional analysis was performed, providing a brief evaluation of the causal effect of IgA nephropathy on complement components. We found a causal effect between C1QBP, C3b, C3d, C2, and C7 and IgA nephropathy, but did not identify any reverse causality. Results from co-localization analysis suggest intricate pathway interactions between the complement system and IgA nephropathy. Our findings provide possible directions for subsequent complement research, which will contribute to further exploration of the etiology of IgA nephropathy.